Neuroelectrophysiological evaluation of carpal tunnel syndrome before and after surgical intervention - Debanjana Chowdhury; Sangita Sen; Tibar Banerjee (Indian Journal of Rheumatology)
Background: Carpal tunnel release operation (CTR) is required to alleviate the symptoms of carpal tunnel syndrome (CTS), the most common entrapment neuropathy. Methods: Thirty-two patients (39 hands) of CTS were subdivided into Group I is moderate CTS (n = 9 hands), Group II is severe CTS (n = 14 hands), and Group III is extreme CTS (n = 16 hands) and underwent conventional electrophysiological evaluation and short segment transcarpal nerve conduction studies preoperatively and 1 and 3 months after open CTR operation. Results: In the case of motor conduction parameter, distal motor latency showed statistically significant improvement after 1 month of CTR (P < 0.05) in all three groups of patients, and improvement consistently increased during 3rd month follow-up (P < 0.001). In Group III patients, preoperatively forearm motor conduction velocity (FMCV) and transcarpal motor conduction velocity (TMCV) were nonrecordable, FMCV became recordable in 6 hands, while TMCV in all 16 hands post CTR. In case sensory parameters, both distal sensory latency (DSL) and sensory nerve conduction velocity (SNCV) showed significant improvement in Group I, and no improvement was noted in Group III patients. Group II (6 of 14 hands) patients showed a reappearance of DSL and SNCV at 1-month follow-up and continued a steady improvement in 3rd month after CTR. Conclusion: We found that TMCV is a more sensitive parameter in assessing improvement of median nerve function after CTR. It is possible to identify patients with a poor outcome by performing electrophysiological studies.